Globalisasi dan Rekonstruksi Identitas: Telaah Filosofis Restorasi Meiji untuk Revitalisasi Budaya Indonesia - Muhtar, Mohamad Khusnial; Ariska, Fitri; Firdaus, Thoriq Baihaqi; Sartini, Sartini (KIRYOKU, 2025)
Globalization is a phenomenon that has brought significant impacts worldwide, including in Indonesia, particularly concerning national cultural identity. Amid this sweeping tide, Japan managed to navigate successfully through its Meiji Restoration. This article explores how the Meiji Restoration model could potentially help Indonesia reconstruct its identity and revitalize its culture. Using a library research method and a philosophical approach, this study reflects on Japan's transformation during the Meiji Restoration, which successfully integrated traditional values with modernity, and compares it to Indonesia's current situation. The findings reveal that social transformation, political reform, and cultural identity reconstruction were key to Japan’s success in overcoming the pressures of globalization. In Indonesia's context, reforming education to instill Indonesian values, adopting flexible cultural preservation strategies, and fostering synergy between the government and society to create sustainable cultural policies are imperative. Indonesia’s cultural identity must be seen as a reflection of the nation's character and mentality, not merely its outward symbols or traditions. This article recommends further research on education models that instill cultural character from an early age, technological strategies for promoting culture, and the integration of traditional values into the creative economy. Such approaches aim to ensure Indonesia’s cultural identity remains strong and relevant amidst global dynamics while thriving on the international stage.